Patient participation in ERS guidelines and research projects: the EMBARC experience - Chalmers, James D. (Breathe (Sheff), 2017)
The European Multicentre Bronchiectasis Audit and Research Collaboration (EMBARC) is a European Respiratory Society (ERS) Clinical Research Collaboration dedicated to improving research and clinical care for people with bronchiectasis. EMBARC has created a European Bronchiectasis Registry, funded by the ERS and by the European Union (EU) Innovative Medicines Initiative Programme. From the outset, EMBARC had the ambition to be a patient-focussed project. In contrast to many respiratory diseases, however, there are no specific patient charities or European patient organisations for patients with bronchiectasis and no existing infrastructure for patient engagement. This article describes the experience of EMBARC and the European Lung Foundation in establishing a patient advisory group and then engaging this group in European guidelines, an international registry and a series of research studies. Patient involvement in research, clinical guidelines and educational activities is increasingly advocated and increasingly important. Genuine patient engagement can achieve a number of goals that are critical to the success of an EU project, including focussing activities on patient priorities, allowing patients to direct the clinical and research agenda, and dissemination of guidelines and research findings to patients and the general public. Here, we review lessons learned and provide guidance for future ERS task forces, EU-funded projects or clinical research collaborations that are considering patient involvement. EDUCATIONAL AIMS: To understand the different ways in which patients can contribute to clinical guidelines, research projects and educational activities. To understand the barriers and potential solutions to these barriers from a physician’s perspective, in order to ensure meaningful patient involvement in clinical projects. To understand the barriers and potential solutions from a patient’s perspective, in order to meaningfully involve patients in clinical projects.